2019
DOI: 10.1111/bjdp.12309
|View full text |Cite
|
Sign up to set email alerts
|

Development of body knowledge as measured by arm differentiation in infants: From global to local?

Abstract: The ability to sense and use the body parts in an organized and differentiated manner is a precursor of body knowledge in infancy. To acquire this ability, the infant's brain might explore the perceptual consequences of its bodily actions. Undifferentiated body movements would gradually be replaced by more precise actions. Only a very few studies have tested this ‘global‐to‐local’ hypothesis, and none of them have so far been replicated. In this study, we assessed arm differentiation in 4‐, 6‐, and 8‐month‐old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(65 citation statements)
references
References 36 publications
5
57
3
Order By: Relevance
“…More specifically, 2-month-old infants increased the movement frequency of all limbs during the acquisition phase, and movement increased in the specific arm connected to the mobile only at 4 months. Similarly, limb differentiation was observed in infants aged 4–8 months in a contingency detection task in which the presentation of an audio-visual stimulus was contingent on the movement of a particular arm (Jacquey et al, 2020b ). Despite the failed attempt of Jacquey et al ( 2020b ) to replicate the developmental trend observed in Watanabe and Taga ( 2006 ), both studies showed that the limb differentiation started at 4 months of age.…”
Section: Recent Yearsmentioning
confidence: 80%
See 4 more Smart Citations
“…More specifically, 2-month-old infants increased the movement frequency of all limbs during the acquisition phase, and movement increased in the specific arm connected to the mobile only at 4 months. Similarly, limb differentiation was observed in infants aged 4–8 months in a contingency detection task in which the presentation of an audio-visual stimulus was contingent on the movement of a particular arm (Jacquey et al, 2020b ). Despite the failed attempt of Jacquey et al ( 2020b ) to replicate the developmental trend observed in Watanabe and Taga ( 2006 ), both studies showed that the limb differentiation started at 4 months of age.…”
Section: Recent Yearsmentioning
confidence: 80%
“…Similarly, limb differentiation was observed in infants aged 4–8 months in a contingency detection task in which the presentation of an audio-visual stimulus was contingent on the movement of a particular arm (Jacquey et al, 2020b ). Despite the failed attempt of Jacquey et al ( 2020b ) to replicate the developmental trend observed in Watanabe and Taga ( 2006 ), both studies showed that the limb differentiation started at 4 months of age. Previous results reported by Rovee-Collier et al ( 1978 ) showed that such limb differentiation is evident even at 3 months.…”
Section: Recent Yearsmentioning
confidence: 80%
See 3 more Smart Citations